EVALUATION OF FETAL THIGH CIRCUMFERENCE AS AN ADDITIONAL MARKER FOR FOETAL BIOMETRY - GUPTA, SARYU; BHARDWAJ,; KAUR, PARAMJEET; GAMBHIR, PUNEET (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Accurate determination of gestational age is the sine qua non of optimal management and hence prognostication of all pregnancies.A meticulous biometry ensures timely interventions resulting in favorable maternal and fetal outcomes. Traditionally, the parameters of Biparietal diameter (BPD), Femur length (FL), Head circumference (HC), and Abdominal circumference (AC) have been utilized for routine fetal biometry. The present study aims to assess the utility of Fetal Thigh Circumference (ThC) as an additional marker for fetal biometry. Methods: The present retrospective, observational, and cross-sectional study was done in the Departments of Radiodiagnosis and Obstetrics and Gynaecology in an ethically and socio-economically diverse group of pregnant females. All pregnant females with singleton pregnancies between 22 and 40 weeks of gestation and fulfilling the inclusion and exclusion criteria were subjected to ultrasound examination. Subsequently analysis was done for the data collected. Results: There were a total of 287 participants in present study group with mean age of 23±3.4 years. The strength of agreement almost perfect (>0.99) between the mean observed ThC to ThC values by Deter et al. taken as standard. There was a highly significant positive correlation between gestational period and standard biometry parameters and ThC. ThC model for prediction will be better than standard biometry parameters of BPD, HC and AC but not as good as FL model according to the regression analysis of the present study. Conclusions: There is concordance of fetal ThC as an accurate predictor of period of gestation only after FL. It can be combined with standard biometry parameters to give a better estimation of period of gestation.